Effects of social power in the development of ambivalent sexism in childhood - Pereira, Ana Carolina dos Santos (2020)
The present investigation explores boys’ and girls’ endorsement of ambivalent sexism (i.e., hostile and benevolent sexism) beliefs when they are in a situation of unequal distribution of power, while taking into consideration a developmental perspective. This study included 218 children, with ages from six to 12-years-old, separated by sex (53.7% female) and into two age groups (i.e., younger and older groups). A power manipulation was carried out in pairs, placing one child in a high-power position and the other in a low-power condition. Among other measures, Children’s Ambivalent Sexism Measure (CASM) was applied. The results revealed significant sex differences on the endorsement of hostile sexism, with boys showing higher endorsement levels than girls. And this effect was qualified by the interaction effect between power condition, sex, age group and ambivalent sexism dimension. Significant age differences on the endorsement of hostile sexism by powerful males were found, with older boys showing higher endorsement levels than younger boys. The findings partially confirm our hypotheses and are discussed considering practical implications.